Personal values and South African financial services brand preference - Steven M. Burgess; Roger D. Blackwell (South African Journal of Business Management, 1994)
Personal values have become an important concept in consumer research. The authors test the value importance-brand preference link, compare brand preference value correlates with the universal content and structure recently proposed by Schwartz, and propose a method of market segmentation based on traditional segmentation criteria and values: The results suggest individual values should remain the focus of consumer research concerning values, that inconsistent patterns of significant values emerge compared to Schwartz's theoretical structure and that values are more important than age, education and household income to an efficient segmentation solution. However, race was the most important segmentation variable and marketers should not disregard it.
Keywords: 650